2003
DOI: 10.1111/j.1365-313x.2004.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐bound fatty acid desaturases are inserted co‐translationally into the ER and contain different ER retrieval motifs at their carboxy termini

Abstract: SummaryFatty acid desaturases (FADs) play a prominent role in plant lipid metabolism and are located in various subcellular compartments, including the endoplasmic reticulum (ER). To investigate the biogenesis of ERlocalized membrane-bound FADs, we characterized the mechanisms responsible for insertion of Arabidopsis FAD2 and Brassica FAD3 into ER membranes and determined the molecular signals that maintain their ER residency. Using in vitro transcription/translation reactions with ER-derived microsomes, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 77 publications
(114 reference statements)
6
143
0
1
Order By: Relevance
“…However, the C-terminal regions of ER-localized desaturases contain ER retrieval motifs (McCartney et al, 2004). Deletion of just five amino acids from the C terminus of the Brassica FAD3 resulted in a dramatic reduction in activity, as well as mislocalization of this protein to the Golgi (McCartney et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the C-terminal regions of ER-localized desaturases contain ER retrieval motifs (McCartney et al, 2004). Deletion of just five amino acids from the C terminus of the Brassica FAD3 resulted in a dramatic reduction in activity, as well as mislocalization of this protein to the Golgi (McCartney et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although these functional complementation results for Cb5 isoforms A, B, and C were expected based upon their localization in the ER in plant cells (Figure 2), the complementation of FAD2 activity by the mitochondrial isoform Cb5-D was surprising. Plant FAD enzymes are localized exclusively in the ER in both plant and yeast cells (Dyer and Mullen, 2001;McCartney et al, 2004), and the ability of Cb5-D to stimulate FAD2 activity suggested that either a proportion of Cb5-D (mis)localized to the ER in yeast cells or that this isoform could donate electrons to ER-bound FADs in trans from the mitochondrial surface. Immunofluorescence microscopic analysis of yeast cells revealed, however, that all four tung myc-tagged Cb5 isoforms localized exclusively to the ER (our unpublished data), indicating that differences in either yeast mitochondrial TA import machinery and/or the cis-acting targeting signals of Cb5-D prevented its sorting to mitochondria.…”
Section: Comparisons Of Cb5 Targeting Among Evolutionarily Diverse Ormentioning
confidence: 99%
“…One equivalent of microsomes (defined as 100 fmol of SRP receptor a-subunit; Andrews et al, 1989) or one equivalent of mitochondria (defined as 50 mg of total mitochondrial protein) were then added to translation reactions and incubated for 1 h at 248C. Import reactions with microsomes were layered onto a 0.5 M sucrose cushion, and membranes were pelleted by centrifugation at 100,000g for 10 min (McCartney et al, 2004). Gradients were fractionated into top and middle fractions (representing soluble proteins), and a bottom fraction was obtained by solubilizing pelleted material (including microsomes and microsomalassociated proteins) in SDS loading buffer.…”
Section: Targeting To Membranes In Vitromentioning
confidence: 99%
See 2 more Smart Citations